Microstructure evolution and mechanical properties of ceramic shell moulds for investment casting of turbine blades by selective laser sintering. Issue 11 (1st August 2018) - Wei, Qian; Zhong, Jiangwei; Xu, Zilin; Xu, Qingyan; Liu, Baicheng
Abstract: Ceramic shell moulds fabricated by traditional shell-making technology have relatively low strength, and often crack during the casting process due to the low strength. In addition, the traditional shell-making process requires long period and high cost. In this work, qualified mullite ceramic shell moulds with enhanced strength were fabricated by selective laser sintering (SLS) combined with high-temperature sintering process. The effects of SLS process parameters on dimensions were investigated, and process optimization was proposed by orthogonal experiments. The effect of sintering temperature on strength at room temperature and 900 °C were studied. X-ray diffraction analysis (XRD) and scanning electron microscopy (SEM) analysis suggested that mullitization behavior was influenced by sintering temperature. Furthermore, the content of mullite phase, mullite grain sizes, and mean length-diameter ratio of the mullite grains increased with the sintering temperature. Mechanical testing results showed that the samples sintered at 1610 °C had an excellent compressive strength of 99.01 MPa at room temperature and over 172.02 MPa at 900 °C. These values far exceed those of ceramic shell moulds fabricated by the traditional shell-making process (40.43 MPa).